Pemberdayaan Masyarakat Melalui Pembuatan Pestisida Nabati dari Daun Kemangi (Ocimum basilicum) Tanpa Fermentasi di Desa Batu Ringgit Kota Mataram Nusa Tenggara Barat - Ardiatun; Mita Yuniangsih; Nurul Aini; Firman Ali Rahman; M. Harja Efendi (Yayasan Tajuk Indonesia, 2024)
Botanical pesticides are an important part of sustainable and environmentally friendly agriculture. The aim of this research is to produce herbal insecticide from basil leaves (Ocimum basilicum) without a fermentation process and test its effectiveness in controlling tomato plant pests (Solanum lycopersicum). Basil leaves contain beneficial substances such as eugenol and flavonoids which can be used as an insect repellent. This community service will be carried out in October 2024 in Batulingit Village, Mataram, West Nusa Tenggara. Integration of basil leaf products as insecticides before people start producing and applying insecticides to tomato plants. The research results show that the use of herbal extracts from basil leaves can significantly reduce the number of pests. Therefore, the use of botanical pesticides not only provides an effective pest control solution, but also supports sustainable agriculture which is better for human health and the environment .